Social networking sites and youth online political participation: a comparative study of Nigeria and Malaysia / Aishat Abdulrauf-Salau, Norsiah Abdul Hamid and Mohd Sobhi Ishak - Abdulrauf-Salau, Aishat; Abdul Hamid, Norsiah; Ishak, Mohd Sobhi (2018)
Researches indicate youth online political participation on Social Networking Sites is the norm in contemporary society. Thus, we compare this phenomenon among youth in two second wave democracies; Nigeria and Malaysia. These countries may not have been focus of much comparative studies of this nature considering their distance geographically, however politically, their similarities are quite significant. Consequently, this gap in comparative research was addressed by the present study. To this end, a survey was conducted on 476 samples in both countries and analysis was carried out using the Partial Least Squares - Multi Group Analysis (PLS-MGA). Accordingly, we find that there is no significant difference between youth in Nigeria and Malaysia in terms of the relationship between Access to Political Information on Facebook and Twitter (APIFT) and Online Political Participation on Facebook and Twitter (OPPFT). However, there is significant difference between Political Interest (PI) and Policy Satisfaction (PS) with youth online political participation on Facebook and Twitter in both countries. Therefore, findings of this present study suggests that despite their national peculiarities there is no difference between the youth in Nigeria and Malaysia in relation to the association between their access to information and online political participation on Facebook and Twitter.